Connected cycles of reflection: The experiential learning process used by youth team sport coaches to develop coaching strategies. - Gilbert, Wade. (University of Ottawa (Canada), 1999)
The purpose of the present study was to describe the process of how youth team sport coaches develop knowledge for coaching through experience. Schon's (1983; 1987) experiential learning theory of reflective practice was used as a conceptual guide. The research design included two focus groups (a pre-study) and multiple-case studies (Yin, 1994). Six coaches of competitive youth team sport comprised the case studies; three in soccer and three in ice hockey. Case study sources of evidence included background interviews, documents, observations combined with video and audio recording, on-site interviews, interval summary interviews, and member check interviews. Data were collected over an entire playing season with each coach. Guided by the case study analytic strategy of relying on theoretical propositions, five methods of qualitative data analysis were used: memos, coding, data displays, interim case summaries, and electronic text searches (Kelle, 1995; Maxwell, 1996; Miles & Huberman, 1994; Yin, 1994). The experiential learning process found in the case studies comprised six components: (a) coaching issues, (b) role frames, (c) issue setting, (d) strategy generation, (e) experimentation, and (d) evaluation. The latter four components comprised a cycle of reflection, referred to as a reflective conversation. Each coach's personal role frame, or approach to coaching, bracketed the reflective conversation, and coaching issues provided the impetus for reflection. The process of identifying an issue, and deciding why it was an issue, is referred to as issue setting. Issue setting included three options: other, peer, and self. Issue setting was proceeded by the strategy generation stage. Six options for generating coaching strategies were found. Three were dependent on coaching peers: advice seeking, joint construction, and reflective transformation. The other three were independent of coaching peers: coaching materials, creative thought, and coaching repertoire. After one or more strategies were generated, an experiment was conducted (real world and/or virtual world). An experiment's effectiveness at resolving a coaching issue was then evaluated. Three options were found at the evaluation stage: other, peer, and self. Once an experiment was evaluated, a coach would either exit the reflective conversation because the issue was resolved or considered unworthy of further reflection, or return immediately to the strategy generation stage to continue the reflective conversation. The selection of options at each stage in a reflective conversation was influenced by four conditions: (a) access to peers, (b) stage of learning, (c) issue characteristics, and (d) environment. The present study provides a first step towards unpacking the frequently cited conclusion that coaches learn through experience. Perhaps the study's most notable contribution to the field of coaching is not the empirically based confirmation that coaches do indeed learn through experience, but an explanation of how coaches learn through experience. Furthermore, when the findings are used to examine other coaching studies, the reflective conversation appears to be valid in other coaching contexts. However, additional research is needed to explore the transferability of the results, and the validity of an experiential learning theory for coaches.
Keywords: Education, Adult and Continuing.